Shadow Banking and Conventional Banks in Financial System Overview - Wibowo, Yohanna Enda (Generate Digital Publishing, 2025)
Objective: This study aims to analyze the relationship between shadow banking and conventional banking in the modern financial system, focusing on their roles, dependencies, and impact on financial system stability. Research Design & Methods: This study uses a qualitative approach, including literature analysis and a theoretical review related to shadow banking and conventional banks. Data was obtained by reviewing various secondary sources, including journals, industry reports, and relevant regulations. Findings: This study found that shadow banking and conventional banks are interdependent despite having different roles in financial intermediation. Shadow banking can increase financial inclusion by providing more flexible financing, but the lack of supervision and transparency can pose systemic risks. In contrast, conventional banks operate under strict regulation, offering stability, but are more limited in terms of flexibility and innovation. Implications & Recommendations: This research recommends strengthening shadow banking regulations, including increased transparency, global regulatory coordination, and consumer protection. Effective regulation is important to balance financial innovation and proper supervision to maintain the global financial system's stability. Contribution & Value Added: This study provides new insights into the dynamic relationship between shadow and conventional banking and its implications for financial stability. It contributes to the understanding of how these two sectors can work synergistically to maintain the integrity of the financial system while encouraging responsible financial innovation.